PENGGUNAAN METODE INTERNALISASI DALAM PEMBELAJARAN ILMU AKHLAK DALAM NASKAH SERAT KIDUNG SESINGIR KARYA PAKUBUWONO IX - Susiyanto Susiyanto; Sudarto Sudarto (Universitas Islam Sultan Agung, 2021)
Internalization is a method used to absorb and instill values so that they are embedded in humans. This method has been used in texts containing moral teachings such as the manuscript of Serat Kidung Sesingir by Pakubuwono IX. The purpose of writing this article is to reveal the use of the Internalization Method in Learning Morals in the Fiber Kidung Sesingir Manuscript by Pakubuwono IX. The method used uses a qualitative approach and utilizes philological methods to present the text and translate it. The result is in step (1). Modeling is carried out using the story method, namely conveying stories from the past and being used for the process of taking orders; (2). Habituation, by inculcating noble character such as diligently working, worshiping, and others; (3). Enforcement of the rules, the author of the manuscript uses examples in the form of direct punishment of a number of religious officials who violate morals; (4). Motivating is carried out according to the level that humans have and the motivation for each person is adjusted to the circumstances of the person concerned.Keywords: internalization, morals, Kidung Sesingir